Victor Juan Guillot’s Detective Stories (Anclajes, 2013)
This paper studies Victor Juan Guillot’s detective stories, hitherto, completely ignored by the literary criticism and the historiography of the detective genre in Argentina. We assert that in these stories it is possible to see the transition from a detective story piece of narrative —which was clearly predominant from late 1870s to 1930s, having melodramatic features and close links with the political and social reality— into a new kind of tale much closer to the English detective story of the Golden Age, and further from empirical national life. In Argentina, this new type of detective chronicle would unfold vigorously during the 1930s and the 1940s. Thus, we attempt to show that the detective stories included in Historias sin importancia (1920) and El alma en el pozo (1925) are in the same line with the early tradition of the genre in Argentina, while the stories included in Terror: cuentos de crimen y misterio (circa 1935) have mostly the same features as those of the 1930s. We also seek to put on view how Guillot’s conception of the detective story in 1925 anticipated Jorge Luis Borges’s conception of the genre in the 30s.
Keywords: Víctor Guillot; Jorge Luis Borges; detective novel; 20th Century; argentinean literature